The Role of the State in Determining the Effectiveness of Environmental Insurance - Lemkowska, Malwina (Olsztyn Economic Journal, 2017)
The concern for the natural environment gives rise to the need for corporate developments toward systemic management tools for environmental risk management, including private insurance. The purpose of this research was to answer the questions: what are the premises for the effectiveness of insurance in environmental risk management and what is / should be the role of the state in the moulding of these premises? It was assumed that effectiveness is a multidimensional concept linked to the subject-centred idea of risk. Description and clarification were performed on the basis of inference as a method of logical reasoning. The attributes of the natural environment and the external effects of human activity validate the state’s intervention in the system of environmental risk management. Additionally, the passive attitude of insurers and the potentially insured increases the need for governmental activity. It may amount to substantive, factual participation or providing stimuli and organising a common platform for cooperation of competent entities. The effectiveness of a macroeconomic risk management system depends on the system’s effectiveness on the micro-level (the degree of fulfilment of goals for insurers and the insured). This argument should be decisive with regards to the selection and structure of the state insurance strategy and its instruments.